Studi Deskriptif Mengenai Kompetensi Guru Yang Mengampu Mata Pelajaran Pengembangan Musik Di SLB 2 Padang - Rangga Ikbal; Erfan Erfan; Yensharti Yensharti (SENDRATASIK UNP, 2019)
This article aims to find out the competence of the teacher who educates Polytechnic music at SLB Negeri 2 Padang. This type of research is qualitative research using descriptive method. The main instrument in this study is the researchers themselves and assisted with the instrument's supporters such as stationery, camera. The technique of data collection is done by way of observation, study of the literature and interviews. The data collected is done analysis with a variety of careful consideration so that the data can be achieved its object and can also be obtained by his righteousness, segingga can answer problems and then made into paper report form thesis. The results showed that the competence of the teachers in Polytechnic study pedagogy at SLB Negeri 2 Padang belongs either. Similarly, with the competence of personality. The teacher has a good personality as well as worthy of dicotoh or be a role model by the learners. Teachers also have the ability of good social as well as professional competence.  By mastering the four competencies of teachers, it can perform the nguru demands his profession as a good educator.